Perinatal outcome associated with oligohydramnios at term - Gandotra, Nikita; Mahajan, Neha; Manhas, Aakriti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Oligohydramnios is a severe and common complication of pregnancy and its incidence is reported to be around 1 to 5% of total pregnancies. The aim of this study was to perinatal outcome of oligohydramnios (AFI <5) at term. Methods: A prospective study was conducted in which 200 patients at term with oligohydramnios AFI <5 cm with intact membranes were analyzed for perinatal outcome. Results: There were increased chances of FHR decelerations, thick meconium, increased LSCS, low Apgar score at 5 minutes, birth weight <2.5 kg, admission to NICU in pregnancy with oligohydramnios. Conclusions: An amniotic fluid index (AFI) of <5 cm detected after 37 completed weeks of gestation is an indicator of poor perinatal outcome. Determination of AFI can be used as an adjunct to other fetal surveillance methods that helps to identify those infants at risk of poor perinatal outcome.